Professional self-determination: Conflict logical aspect - Andrey Georgievich Bolshakov, Victoria Ravilꞌevna Sagitova, Andrey Valeryevich Ivanov, (Opción, 2019)
The purpose of the study is to cover the issue of professional self-determination from the standpoint of a conflictological approach via comparative qualitative research methods. As a result, the conflict of inadequate self-esteem arises because of the discrepancy between the claims of an individual and the assessment of their capabilities. In conclusion, identification becomes a trigger for a crisis in the development of a profession or in its implementation, which entails the conflicts of an interpersonal and intrapersonal nature.